COMORBIDITIES IN PRACTICE. CLINICAL GUIDELINES - R. G. Oganov; I. N. Denisov; V. I. Simanenkov; I. G. Bakulin; N. V. Bakulina; S. A. Boldueva; O. N Barbarash; N. P Garganeeva; V. L Doshchitsin; O. M. Drapkina; E. N. Dudinskaya; Yu. V. Kotovskaya; et al. (Кардиоваскулярная терапия и профилактика, 2017)
.